The endogenous Mtv8 locus and the immunoglobulin repertoire - Beilinson, Helen A.; Erickson, Steven A.; Golovkina, Tatyana (Frontiers in Immunology, 2024)
The vast diversity of mammalian adaptive antigen receptors allows for robust and efficient immune responses against a wide number of pathogens. The antigen receptor repertoire is built during the recombination of B and T cell receptor (BCR, TCR) loci and hypermutation of BCR loci. V(D)J recombination rearranges these antigen receptor loci, which are organized as an array of separate V, (D), and J gene segments. Transcription activation at the recombining locus leads to changes in the local three-dimensional architecture, which subsequently contributes to which gene segments are utilized for recombination. The endogenous retrovirus (ERV) mouse mammary tumor provirus 8 (Mtv8) resides on mouse chromosome 6 interposed within the large array of light chain kappa V gene segments. As ERVs contribute to changes in genomic architecture by driving high levels of transcription of neighboring genes, it was suggested that Mtv8 could influence the BCR repertoire. We generated Mtv8-deficient mice to determine if the ERV influences V(D)J recombination to test this possibility. We find that Mtv8 does not influence the BCR repertoire.